Operator-norm approximations of holomorphic one-parameter semigroups of contractions in Hilbert spaces - Arlinskii, Yu. M. (Methods of Functional Analysis and Topology, 2012)
We establish the operator-norm convergence of the Iosida and Dunford-Segal approximation formulas for one-parameter semigroups of the class C_0, gene ated by maximal sectorial generators in separable Hilbert spaces. Our approach is essentially based on the Crouzeix-Delyon theorem [8] related to the generalization of the von Neumann inequality.